2012
DOI: 10.1002/dneu.20961
|View full text |Cite
|
Sign up to set email alerts
|

Maternal stress induces adult reduced REM sleep and melatonin level

Abstract: Objectives We have previously reported that neonatal maternal deprivation (MD) resulted in a decrease of total sleep and an increase of orexin A in adult rats. Now, we characterized features of sleep, activity, and melatonin levels in rats neonatally treated with MD and control (MC) procedures. Design Adult male Sprague Dawley rats were treated with either MD or MC procedures for ten days starting at postnatal day 4. At three months of age, sleep was recorded for 48 hours in one set of MD and MC rats while a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…In this study, we have shown that adult rats that were subjected to MS exhibited increased W and reduced sleep in the spontaneous sleep-wake cycle, as has been documented previously [4,6] (Fig. 1).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, we have shown that adult rats that were subjected to MS exhibited increased W and reduced sleep in the spontaneous sleep-wake cycle, as has been documented previously [4,6] (Fig. 1).…”
Section: Discussionsupporting
confidence: 87%
“…As we have previously discussed, stressful events in early life, such as MS, result in enhanced W and reduced sleep during adulthood [4]; in addition, this stress-related animal model has been shown to induce long-lasting neurochemical changes, and the lateral hypothalamus, a brain structure that is involved in the maintenance of W [8], seems to be sensitive to this phenomenon. In this regard, it has been reported that MS induces an increase in hypothalamic OX [16].…”
Section: Discussionmentioning
confidence: 82%
“…morningness versus eveningness) and sleep disorders, as well as medication, might have an impact on the growth of fetal PGV, resulting in smaller pineal glands in the newborn which, again, might cause sleep disturbances in the years to come. One study in primates (Seron‐Ferre et al ., ) and one in rodents (Feng et al ., ) provided evidence that certain conditions during pregnancy might influence the development of the newborn circadian system and its components. Similar findings have been demonstrated in other animal studies (reviewed in Seron‐Ferre et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] Recent evidence indicates that sleep disturbance is one of the long-term effects of early-life stress [3] based on consistent association between childhood adversities and poor sleep quality in adult humans [46] and rodents. [7,8] Given that sleep disturbance causes a severe burden on individuals and society and constitutes an early predictor of the future development of emotional and cognitive disorders, [9,10] understanding how early-life stress influences sleep behaviors has significant clinical importance.…”
Section: Introductionmentioning
confidence: 99%